Aprimoramento das condições operacionais para a síntese de oligossacarídeos por Β-Galactosidase de Kluyveromyces lactis a partir de soro de leite - Silva, Natan Câmara Gomes e (2021)
Functional foods can be defined as beneficial compounds to the human body and that can act in the prevention of certain chronic diseases. One of the main compounds are the oligosaccharides, especially lactulose. This compound has beneficial characteristics to the human body, contributing to the treatment and prevention of diseases related to the gastrointestinal tract. There are already ways of obtaining it from biochemical pathways, which allow the use of non-pure substrates, such as by-products or industrial waste, including whey, which is a low-cost by-product of the dairy industry and high potential for use in this type of process. In this context, the present study aimed to evaluate different operational conditions to improve the production of oligosaccharides by β-galactosidase from Kluyveromyces lactis immobilized on chitosan, using whey as a substrate. Enzymatic immobilization in chitosan was performed following an activation protocol with 0.8% glutaraldehyde (v/v). The results showed that the best load of protein used in the immobilization was 7 mg/g, resulting in a biocatalyst with an activity of 44.29 ± 0.95 U/g. The transgalactosylation activity of the enzyme was also determined, which was 56,837 ± 487.32 Ulactulose/genzyme. In the production of lactulose and/or oligosaccharides, with pure reagents, the effect of the initial substrate lactose:fructose ratio was evaluated and the best ratio evaluated was 1:2 for both forms of catalyst, free or immobilized. The percentage of lactose hydrolysis was 96.02% and 97.86%; 15.51 g/L and 13.20 g/L of lactulose produced and a lactulose production yield of 0.20 and 0.21 glactulose/glactose, using free and immobilized enzyme, respectively. The studies with whey showed that the best results were also obtained in the 1:2 ratio of lactose:fructose. The hydrolysis percentages were 95.39% and 96.56%; 20.77 g/L and 9.01 g/L of lactulose produced with yields of 0.33 and 0.14 glactulose/glactose, respectively in studies with free and immobilized enzymes. In addition to these studies, processes were carried out that involved the previous incubation of the biocatalyst at the reaction temperature and in the presence of the components of the reaction medium. A previous incubation of the biocatalyst at a temperature of 50°C was positive for the process when temperatures below the optimal reaction were used, with an increase of 40.74% and 26% in lactulose production when the process was conducted at 25°C and 37°C, respectively. Regarding the enzymatic incubation in media with the substrates, there was an improvement in the levels of lactulose produced at 25°C, when the biocatalyst was incubated in buffer and in lactose. Once the best conditions were established, a proposal for process integration was sought, using different operational configurations and other biocatalysts, such as glucose-isomerase from S. murinus. Batch reactors were used, following different reaction schemes. The results were lower than expected, but oligosaccharides were produced, such as lactulose (1.24 g/L) and raffinose (3.16 g/L). The hydrolysis steps were efficient, indicating the need to move to new operational strategies in order to optimize the integration of processes. Thus, initial studies in fixed bed reactors (using pure reagents) were carried out and the hydrolytic percentages obtained in the continuous processes were 96%, with a glucose and galactose production of 41.64 and 42.14 g/L, respectively, obtained after the process enters the steady state, with little variation in concentration after 3.5 hours of reaction in the bed. The process of isomerization of the released glucose by glucose-isomerase from S. murinus was also evaluated. The isomerization studies in a fixed-bed reactor, using pure glucose and hydrolyzed whey, were also efficient, producing a fructose concentration of approximately 46.13 g/L and 35.19 g/L, respectively, after entry into the stationary state. In addition to these studies, the reduction of protein load in the immobilization process was evaluated in order to reduce the effects of a possible reverse hydrolysis of the formed products, showing that this reduction improved the production levels of lactulose, as well as raffinose. The results obtained indicate the beginning of a promising process for the use of an industrial by-product to obtain compounds with greater added value. Key-words: Oligosaccharides